Conducta obstétrica en paciente primigesta de 17 años con embarazo de 36.5 semanas y amenaza de parto pretérmino. - Morla Anchundia, Lessly Jelipsa (2022)
The purpose of this study was: to identify the main maternal risk factors associated with: threat of preterm delivery in a 17-year-old primigravid woman at 36.5 weeks of gestation. The risk of preterm delivery in the general population is estimated to be between 6% and 10%. According to the Pan American Health Organization (PAHO), in Ecuador the INEC reported 15,185 cases of threatened preterm labor, which were registered as false labor (ICD-10 O.47), these cases constituted 0.22% of hospital admissions nationwide. The threat of preterm labor, both globally and locally, is associated with significant morbidity and serious complications, thus its investigation constitutes a research tool to identify those susceptible maternal organisms. Methodology.- For the selection of the case, the observation of the Clinical History was made, which was obtained from the statistical area of the Basic Hospital of Liberty "Dr. Rafael Serrano López” confidentiality was kept since a numerical code was assigned to identify the patient. For theoretical support, a bibliographic review of the clinical practice guidelines of the Ministry of Public Health, indexed journals of the academic Google was carried out, it was detected as risk factors for premature rupture of membranes, cervico-vaginitis, urinary tract infection and anemia. The obstetric management applied is that every patient who consults the emergency room due to uterine contractions will be evaluated by baseline monitoring, to verify the presence of uterine contractions, evaluation of the fetal heart rate, vaginal touch to evaluate cervical conditions, transvaginal ultrasound to measure the cervix length, hospitalization, lung maturation. The delivery route was vaginal, the maternal outcome was favorable, without complications and the fetal outcome was a single live birth.